Acetyl-DL-leucine in Niemann-Pick type C: A case series. (20th October 2015) - Bremova, Tatiana; Malinová, Věra; Amraoui, Yasmina; Mengel, Eugen; Reinke, Jörg; Kolníková, Miriam; Strupp, Michael
Abstract : Objective: To assess the effects of the modified amino acid acetyl-DL-leucine (AL) on cerebellar ataxia, eye movements, and quality of life of patients with Niemann-Pick type C (NP-C) disease. Methods: Twelve patients with NP-C disease were treated with AL 3 g/d for 1 week and then with 5 g/d for 3 weeks with a subsequent washout period of 1 month. The Scale for the Assessment and Rating of Ataxia (SARA), the Spinocerebellar Ataxia Functional Index (SCAFI), the modified Disability Rating Scale (mDRS), EuroQol 5Q-5D-5L, and the visual analog scale (VAS) were administered. Measurements took place at baseline, after 1 month of therapy, and after 1 month of washout. Results: The SARA score changed from the baseline (median [±SD, interquartile range]) of 10.8 (11.2, 8–24.6) to 7.0 (10.7, 5.6–19.6) on medication (difference: 3.8 points) and 10.5 (11.5, 7.1–23.9) after washout (difference: 3.5 points) ( p = 0.000412; post hoc p = 0.003 between baseline and on medication, and on medication and washout p = 0.005). The SCAFI subscore 9-Hole Peg Test for dominant hand, mDRS score, and VAS score also improved on medication. No side effects except transient dizziness in one patient were reported. Conclusions: Treatment with AL improved ataxic symptoms in patients with NP-C without relevant side effects, thus showing a reasonable risk-benefit profile. Classification of evidence: This study provides Class IV evidence that AL improves cerebellar symptoms and quality of life in patients with NP-C.